2008
DOI: 10.1021/jp8031034
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanisms of C2Cl3 + NO2 via Nitro and Nitrite Adducts

Abstract: The atmospherically and environmentally important reaction of chlorinated vinyl radical with nitrogen dioxide (C 2 Cl 3 + NO 2 ) is investigated by step-scan time-resolved Fourier transform infrared emission spectroscopy and electronic structure calculations. Vibrationally excited products of CO, NO, Cl 2 CO, and NO 2 are observed in the IR emission spectra. Geometries of the major intermediates and transition states along the potential energy surface are optimized at the B3LYP/6-311G(d) level, and their energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…According to its spectral position, the intense emission band from 1740 to 1920 cm À1 (band I) are most likely ascribed to the C-O stretching mode of Cl 2 CO (fundamental frequency at 1827 cm À1 ), which are predicted to be the major products theoretically. This IR emission band due to Cl 2 CO has also been observed in the reaction of C 2 Cl 3 with O 2 9 and NO 2 11 in our previous studies. The assignment of this band to another possible species with fundamental frequency at 1884 cm À1 , ClCO, 34 can be ruled out.…”
Section: Experimental Observation Of the Reaction Productssupporting
confidence: 86%
See 2 more Smart Citations
“…According to its spectral position, the intense emission band from 1740 to 1920 cm À1 (band I) are most likely ascribed to the C-O stretching mode of Cl 2 CO (fundamental frequency at 1827 cm À1 ), which are predicted to be the major products theoretically. This IR emission band due to Cl 2 CO has also been observed in the reaction of C 2 Cl 3 with O 2 9 and NO 2 11 in our previous studies. The assignment of this band to another possible species with fundamental frequency at 1884 cm À1 , ClCO, 34 can be ruled out.…”
Section: Experimental Observation Of the Reaction Productssupporting
confidence: 86%
“…3(c), these two bands are rotationally irresolvable at the spectral resolution of 0.5 cm À1 , suggesting that they are not originated from diatomic products of NO and CO although their IR bands also fall within these spectral ranges, because rotationally resolved structure should be well resolved for NO and CO at 0.5 cm À1 . 11 Instead, these unresolved bands should be ascribed to polyatomic molecules. The assignment of these structureless bands is made possible with the aid of our theoretical calculations which have predicted the feasible reaction products.…”
Section: Experimental Observation Of the Reaction Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…CH3NO2 33 , CHCl2NO2 34 and C2Cl3NO2 35 . The authors showed that NO2 and the carbon radicals (CH3, CHCl2 or C2Cl3) react by combination to form either the reactant (addition of the N side of NO2) or a R-ONO species (addition of the O side of NO2).…”
Section: Mechanism Specific To Chloropicrinmentioning
confidence: 99%
“…The kinetic constant of the first reaction was estimated from the correlations involved in the EXGAS software and that of the second one by analogy with the reaction CCl 3 + Cl, which produces a C–Cl bond with a close BDE. Decomposition reactions of the produced radicals were included, based on analogueies with species featuring similar chemical structures, like CH 3 NO 2 , CHCl 2 NO 2 , and C 2 Cl 3 NO 2 . The authors showed that NO 2 and the carbon radicals (CH 3 , CHCl 2 , or C 2 Cl 3 ) react by combination to form either the reactant (addition of the N side of NO 2 ) or a RONO species (addition of the O side of NO 2 ).…”
Section: Mechanism Specific To Chloropicrinmentioning
confidence: 99%